ISAR-LEFT MAIN 2 Trial: Zotarolimus- versus Everolimus- Eluting Stents for Treatment of Unprotected Left Main Coronary Artery Lesions - Rizzo, Toni (MD Conference Express, 2012)
The original Drug-eluting Stents for Unprotected Left Main Stem Disease [ISAR-Left Main] study found no significant difference in outcomes for patients with unprotected left main coronary artery stenosis (uLMCS) who were treated with first generation paclitaxel-eluting versus sirolimus-eluting stents [Mehilli J et al. J Am Coll Cardiol 2009]. The objective of the current ISAR-LEFT MAIN 2 trial [NCT00598637] was to compare the performance of zotarolimus-eluting stent versus everolimus-eluting stent in patients with uLMCS lesions, using a noninferiority design.